Optimalisasi Perilaku Asertif Melalui Media Modul Bimbingan dan Konseling - Annisa Arrumaisyah Daulay; Daharnis Daharnis; Afdal Afdal (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2021)
This research was conducted to develop a proper guidance and counseling module that can be used by counselor as a media to develop assertive behavior. Aims of this research is to: produce guidance and counseling module to develope assertive behavior that is valid in contents and apperance and describes the usefulness level of the guidance and counseling module to develop assertive behavior. The method use was ADDIE model development. Subject trial consisted of 3 experts to test feasibility, 5 counselors, and 30 students to test usefulness of the module. This research was conducted by trying out the product and group discussion. The data were analyzed by using statistics descriptive and nonparametric analysis. Based on these result showed that the guidance and counseling module to developed students assertive behavior is valid in contents and appearance. The usefulness level of the guidance and counseling assertive behavior module was in very good category.